Long-term impairment of neurovascular coupling following experimental subarachnoid hemorrhage. Issue 6 (June 2020) - Balbi, Matilde; Vega, Max Jativa; Lourbopoulos, Athanasios; Terpolilli, Nicole A; Plesnila, Nikolaus
CO2 -reactivity and neurovascular coupling are sequentially lost within the first 24 h after subarachnoid hemorrhage (SAH). Whether and when these impairments recover is not known. Therefore, we investigated the reactivity of pial and intraparenchymal vessels by in vivo two-photon microscopy one month after experimental SAH. C57BL/6 mice were subjected to either sham surgery or SAH by filament perforation. One month later, cerebral blood flow following CO2 -challenge and forepaw stimulation was assessed by laser Doppler fluxmetry. Diameters of pial and intraparenchymal arterioles were quantified by in vivo two-photon microscopy. One month after SAH, pial and parenchymal vessels dilated in response to CO2 . Neurovascular coupling was almost completely absent after SAH: vessel diameter did not change upon forepaw stimulation compared to a 20% increase in sham-operated mice. The current results demonstrate that neurovascular function differentially recovers after SAH: while CO2 -reactivity normalizes within one month after SAH, neurovascular coupling is still absent. These findings show an acute and persistent loss of neurovascular coupling after SAH that may serve as a link between early brain injury and delayed cerebral ischemia, two distinct pathophysiological phenomena after SAH that were so far believed not to be directly related.